Effects of Ions-DNA Interactions on Surface Charge of Graphene FieldEffect Transistor - Sandrasagran, Gohvinath (Universiti Teknologi PETRONAS, 2021)
Graphene Field Effect Transistors (GFET) are currently being used in many sensing applications due to its high sensitivity and good selectivity. In this project, GFET properties and characteristics will be discussed and compared with other field effect transistors (FET). More importantly, biomolecular electrostatic calculation will be carried out to determine mean electrostatic potential energy, binding energy, and solvation energy. These biomolecular electrostatic calculations will be done using the Poisson-Boltzmann equation coded in MATLAB. Next, study on how these parameters affect ion-DNA interaction and the surface charge on GFET will be carried out by modelling the GFET based on drift-diffusion (DD) model using MATLAB. From the Poisson-Boltzmann equation, the electrostatic potential energy contained within a single strandguanine DNA is found to be 120213 kJol/mol while binding energy and solvation energy are 119991 kJol/mol and 3509.09 kJol/mol, respectively. From drift-diffusion model, the potential on the surface that is needed to cause a shift in the charge neutrality point by 3.5V, is estimated to be -15mV. The outcome of this project should be able to shed some light on how the sensitivity and selectivity of GFET can be furtherimproved.